2010
DOI: 10.4049/jimmunol.1000776
|View full text |Cite
|
Sign up to set email alerts
|

PLZF Induces the Spontaneous Acquisition of Memory/Effector Functions in T Cells Independently of NKT Cell-Related Signals

Abstract: The broad complex, tramtrack, bric-a-brac–zinc finger (BTB-ZF) transcription factor promyelocytic leukemia zinc finger (PLZF) is required for development of the characteristic innate/effector functions of NKT cells. In this study, we report the characterization and functional analysis of transgenic mouse T cells with forced expression of PLZF. PLZF expression was sufficient to provide some memory/effector functions to T cells without the need for Ag stimulation or proliferation. The acquisition of this phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 57 publications
6
102
0
2
Order By: Relevance
“…S6). Previous studies have suggested that PLZF expression is tightly regulated during iNKT cell development, and is down-regulated following maturation of iNKT cells to stage 3 (17,29,30). In line with this, we found that PLZF expression in WT mice was downregulated during the transition from stage 2 to stage 3 ( Fig.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…S6). Previous studies have suggested that PLZF expression is tightly regulated during iNKT cell development, and is down-regulated following maturation of iNKT cells to stage 3 (17,29,30). In line with this, we found that PLZF expression in WT mice was downregulated during the transition from stage 2 to stage 3 ( Fig.…”
Section: Resultssupporting
confidence: 77%
“…PLZF expression was persistently elevated in of late iNKT cell markers, such as CD122, NK1.1, and NKG2D (17,29,30). These studies suggest that iNKT cell development is exquisitely sensitive to levels of PLZF.…”
Section: Discussionmentioning
confidence: 67%
“…PLZF defines not merely the phenotype of iNKT cells, it directs their effector program and is implicated in their proapoptotic propensity (16,39,40). Transgenic expression of PLZF during T cell development induced a T cell-intrinsic program leading to an increase in peripheral CD44 high memory/effector T cells (41,42). These transgenic T cells could produce large amounts of several cytokines upon primary activation without further peripheral polarization, which suggests that PLZF directly turns on the effector program in thymocytes that otherwise would have been selected as naive T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to iNKT cells, PLZF controls other lymphoid effector programs and is involved in many major developmental and biological processes, such as megakaryocytic development, stem cell renewal, limb development, and tumorigenesis (8,(32)(33)(34)(35). PLZF nuclear localization to the NBs has been proposed to be important for its function.…”
Section: Significancementioning
confidence: 99%